Intraosseous injection of SMNP vectors enables CRISPR/Cas9-mediated knock-in of HBB gene into hematopoietic stem and progenitor cells. (December 2022) - Ban, Qian; Lee, Junseok; Shi, Zhenni; Lu, Daoqiang; Qiao, Li; Yang, Peng; Li, Xiaofeng; Cheng, Hongya; Zhang, Meng; Hou, Jinbin; Yao, Jenna H.; Wang, Jun; et al.
Abstract: β-Hemoglobinopathies are hereditary diseases originating from mutations in the hemoglobin beta (HBB) gene. Allogeneic transplantation of hematopoietic stem cells (HSCs) is the only approved treatment to date providing a cure, which is limited due to low histocompatibility from potential donors. Although several clinical trials are introducing the functional HBB gene into autologous HSCs, the ex vivo viral transfection method raises safety concerns for clinical translation. Here, we reported a novel strategy that features direct bone marrow delivery of a CRISPR/Cas9-mediated knock-in system that integrates a copy of the functional HBB gene to the genome by supramolecular nanoparticle (SMNP) nonviral vectors. We demonstrated the feasibility of SMNP vectors for the delivery of the knock-in system. First, the biodistribution of SMNPs was monitored after intraosseous (i.o.) injection in a mouse model. Second, the in vitro CRISPR/Cas9-mediated knock-in of the HBB/GFP gene via SMNP vectors was evaluated in mouse stem cells. Finally, in vivo CRISPR/Cas9-mediated knock-in of mouse hematopoietic stem and progenitor cells (HSPCs) was performed by i.o. injection of SMNP vectors into mouse bone marrow. We believe this strategy presents a unique and innovative approach to treating β-hemoglobinopathies. Graphical Abstract: This platform offers a general therapeutic solution for β-hemoglobinopathies by CRISPR/Cas9-mediated knock-in of the HBB/GFP gene into hematopoietic stem and progenitor cells (HSPCs). Intraosseous injection of two supramolecular nanoparticle (SMNP) vectors co-delivers two DNA plasmids, a Cas9/sgRNA construct and HBB/GFP, into bone marrow, enabling integration of the HBB/GFP gene into genomic DNA of the HSPCs via homology-directed repair (HDR) pathway. ga1 Highlights: Our strategy enables CRISPR/Cas9-mediated knock-in of HBB gene into HSPCs. Successful uptake and clearance of the SMNP vectors are observed. Nonviral SMNP can deliver the HBB/GFP gene knock-in system into stem cells. Durable expression of the HBB/GFP gene is demonstrated. SMNP vectors show the potential for local delivery of the genomic materials.